2012
DOI: 10.1039/c2cs35094g
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polymers and their therapeutic potential

Abstract: The last decade has witnessed enormous research focused on cationic polymers. Cationic polymers are the subject of intense research as non-viral gene delivery systems, due to their flexible properties, facile synthesis, robustness and proven gene delivery efficiency. Here, we review the most recent scientific advances in cationic polymers and their derivatives not only for gene delivery purposes but also for various alternative therapeutic applications. An overview of the synthesis and preparation of cationic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
441
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(457 citation statements)
references
References 353 publications
(305 reference statements)
6
441
0
2
Order By: Relevance
“…Since more than a decade, pharmacists, material scientists and biophysicists are intensively studying the design, preparation and cell biological behavior of nanosized particles carrying nucleic acids (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Since more than a decade, pharmacists, material scientists and biophysicists are intensively studying the design, preparation and cell biological behavior of nanosized particles carrying nucleic acids (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Cationic polymers have also been proposed as nonviral gene delivery systems, due to their flexible properties, facile synthesis, robustness and proven gene delivery efficiency. For further details about the most recent scientific advances in cationic polymers and their derivatives not only for gene delivery purposes but also for various alternative therapeutic applications, the reader is directed to the review in [179]. The use of liposomes combined with scaffolds may contribute to overcoming the issues of toxicity, long-term expression and silencing efficiency.…”
Section: Therapeutic Gene Deliverymentioning
confidence: 99%
“…The surface charge on NPs plays an important role in the way NPs interact with cell surfaces, and it has been reported that cationic particles generally enhance cellular uptake. 8,9 Moreover, NPs are able not only to function as a sonosensitizer per se, but also as energy transducers. 10 Therefore, we engineered poly-methyl methacrylate coreshell NPs so as to load the meso-tetrakis (4-sulfonatophenyl) porphyrin (TPPS) onto their cationic surface to form an innovative sonosensitizing system, ie, TPPS-NPs.…”
Section: Introductionmentioning
confidence: 99%